Democratisation in Malaysia: The impact of social media in the 2008 general election - Mohd Sani, Mohd Azizuddin; Zengeni, Knocks Tapiwa (2010)
The proliferation of social media such as blogging and online news portals has ramifications for national security, spanning future operating challenges of a traditional, irregular and disruptive nature.There is no doubt that the Internet is a conduit for alternative information and democratic values because it helps people to evade the intrusive force of censorship.It increases transparency by facilitating the flow of information about government.In the case of Malaysia during the 12th general election in 2008, social media was definitely an important instrument in promoting democracy. It opens up the space for the Malaysian citizens to deliberate political issues and gave the opportunities for the opposition to utilize in influencing the election result. The government was under estimated the influence of social media to the Malaysian voters. With the policy of free cyberspace, the social media has huge potential to strengthen the democratization process and democracy in Malaysia.